THE EASY WAYS OF LEARNING MEDICAL PLANTS (PHYTONYMS) IN THE DEPARTMENT OF PHARMACEUTICAL TERMINOLOGY (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2021)
This article will discuss the methods of easy study and teaching students of higher medical educational institutions the names of medicinal plants (phytonyms) in the discipline of Latin and medical terminology in the section of pharmaceutical terminology.